Comparative Analysis Of Balances Of Payments Of Ukraine And Poland In The Post-crisis Economic Environment - Lypko, Nazariy (Comparative Economic Research. Central and Eastern Europe, 2014)
The condition of a country’s balance of payments is a crucial factor for effective development in small open economies, such as Poland and Ukraine. Because of their dependence on the climate in international markets, Poland and Ukraine are especially vulnerable to fluctuations in the global situation. Thus it is essential for both national economies to develop effective instruments for adjusting their balance of payments accounts. This necessity in turn requires research into the main mechanisms used for making balance of payments adjustments for developing countries, since not all aspects have been yet explored. A comparative analysis of the balance of payments situations in these countries is conducted in this article, which aims to prove external similarities between both countries and explain why Poland has attained greater success in the process of overcoming the consequences of the global financial crisis. Such conclusions can be used as a roadmap for Ukraine on its way to adjustment of its balance of payments account. The main reason for such exploration is that Ukraine’s balance of payments is still operating in deficit conditions, which negatively affects the overall state of the national economy of the country.